Morphometry, stereology and liver biochemistry tests in infant albino rats submitted to residual ingestion of pregabalin in breast milk (Research, Society and Development, 2021)
This study has evaluated the effects of pregabalin on the liver of lactating rats, derived from the offspring of mothers who received the drug during lactation. Twenty-four albino lactating rats with 14 and 21 days of life were used. They were divided into control (CG) and pregabalin (PG) groups, and these were subdivided according to the age at euthanasia (CG14, CG21, PG14, PG21). The lactating mothers of the treatment group received, orally, the psychotropic drug pregabalin during the 21 days of nursing. The ones of the control group received only saline solution. On the date of euthanasia, morphometric and stereological values were measured. The samples were fixed and liver sections were processed. Area and diameter of hepatocyte nuclei; area of hepatocytes; area and diameter of bile ducts; and the number of hepatocytes per area; as well as volume densities of hepatocytes, and interstitial tissue were obtained. The results were compared by the Mann-Whitney U statistical test, for variables with non-parametric distribution, and Student's t-test for parametric variables. Animals in the treatment group showed an increase in biometric variables at both ages studied. There was an increase in the area of hepatocytes at 14 and 21 days of life, and an increase in the diameter of the hepatocyte nuclei of euthanized animals at 21 days of age. There was an increase in the volume of liver tissues in the 14-day-old group. Liver enzymes were unchanged. Pregabalin promoted hepatocyte hypertrophy (Megalocytosis) without compromising the functional activity of the cells.